I learnt a whole lot more than churning out an essay: Using online tools to support critical collaborative inquiry in a blended learning environment - Elaine Khoo; E. Marcia Johnson; Anne Zahra (Flexible Learning Association of New Zealand, 2012)
This paper reports on a qualitative case study of a teacher and her students in a postgraduate Tourism course in New Zealand in which a Learning Management System (LMS), discussion forums, and wikis were used to facilitate student engagement and deeper learning of course content. Although the teacher was experienced in face-to-face teaching contexts, she was a novice in the design and delivery of online learning. However, she believed that technology could foster deeper and more meaningful critical collaborative inquiry amongst course participants and was keen to explore how this could be facilitated. Evaluative data were gathered from teacher interviews, student focus groups, and an online student survey. Findings indicate that the use of different online tools was effective for engaging students and helped them develop critical insights into key course concepts. However, careful planning and reflection on different pedagogical approaches were needed so that student learning could be supported in a meaningful and relevant ways. Implications for supporting educators and students in blended, online learning in Tourism Education are offered.